GALERI SENI DAN BUDAYA DAYAK KALIMANTAN BARAT - Bayu Indrabuana; Valentinus Pebriano; Lestari Lestari (JMARS: Jurnal Mosaik Arsitektur, 2022)
Art and culture were born from human civilization. Humans must of course maintain and preserve the arts and culture inherited from their ancestors. A pattern of thought is needed so that art and culture are maintained and developed. In West Kalimantan, especially the Dayak tribe, they have various artistic and cultural potentials with the emergence of various agendas in the life of the Dayak group. This paper aims to create a recreational and educational forum that represents the agenda of Dayak art and culture. The method used in designing the West Kalimantan Dayak art and culture gallery in Kubu Raya Regency consists of various stages such as the idea stage to the stage of collecting data related to the required design needs. The result of the design of the West Kalimantan Dayak art and culture gallery in Kubu Raya Regency is a single building with the basic form of a long house and an area that represents the environment of the Dayak tribe through forest and river parks with the main function of the gallery and supporting facilities in it. The West Kalimantan Dayak art and culture gallery area displays the functions of promotion, education, recreation, and information that is able to support various arts and presents various distinctive reflections on Dayak architecture in West Kalimantan.